Akkermansia muciniphila May Determine Chondroitin Sulfate Ameliorating or Aggravating Osteoarthritis - Wang, Qi; Huang, Shui-Qing; Li, Chang-Qing; Xu, Qin; Zeng, Qing-Ping (Frontiers in Microbiology, 2017)
Chondroitin sulfate (CS) has shown either ameliorating or aggravating effects on osteoarthritis (OA) in separately conducted clinical trials. Because CS is usually administered orally, it should be affected by or would impact on the individual gut microbiota. Evidence is accumulating that CS can flourish sulfatase-secreting bacteria (SSB) and sulfate-reducing bacteria (SRB). To decipher how can an individual gut microbiota determine the clinical values of CS for treatment on OA, we suggest here that CS would give distinct outcomes for OA treatment depending on Akkermansia muciniphila, a gut commensal probiotic bacterial species as optimal presence albeit also behaving as mucus-eroding bacteria (MEB) when abundant presence. Briefly, CS would ameliorate OA if A. muciniphila is present due to without overgrowth of SSB and SRB, whereas CS would aggravate OA if A. muciniphila is absent because of failure in competition with abundant SSB and SRB. By noting such a frequently ignored phenomenon, we urge the development of non-orally administering CS to minimize its side-effects and extend it to other medicinal applications.